Potential Effects of Methane Metabolic Microbial Communities on the Glacial Methane Budget in the Northwestern Tibetan Plateau - Yuchan Guo; Shuhong Zhang (Sustainability, 2023)
With global warming, the dramatic retreat of glaciers in the Tibetan Plateau (TP) might accelerate release of stored methane (CH4) into the atmosphere; thus, this region might become a new source of CH4. CH4-metabolic microbial communities can produce or consume CH4 in the environment, which is critical for evaluating the CH4 budget of glaciers. However, studies on the influence of CH4-metabolic microbial communities on the CH4 budget during glacier retreat in the TP remain scarce. In this work, ice samples were collected at the terminus of the Guliya Ice Cap in the northwestern TP. The community composition of CH4-metabolic microorganisms, including methanogens and methanotrophs, was determined using genomic analysis, and the metabolic rates of the two microorganisms were further estimated. The abundance of methanotrophs in Guliya was one order of magnitude higher than that of methanogens. The CH4 consumption flux by the combined action of the two microorganisms was ca. 1.42 × 103 pmol·mL−1·d−1, suggesting that CH4 metabolic microbial communities in the glacier might be an important CH4 sink, and can reduce subglacial CH4 emission during glacier retreat. This is important for predicting the CH4 budget in glaciers on the TP and corresponding climate impacts during glacier retreat.